Sediment characteristics of Van Veen samples of MEDWAVES expedition (H2020 ATLAS project) - José Luis Rueda; Javier Urra; Marina Gallardo-Núñez; Ángel Mateo-Ramírez; Covadonga Orejas (PANGAEA, 2018)
The present data shows the main sediment characteristics (sediment type and colour), as well as some details of the biota detected, in different seamounts that were studied within the framework of the MEDWAVES expedition (H2020 ATLAS project), between September and October 2016. A total of four box-corer (BC) samples were collected at Gazul mud volcano (Gulf of Cadiz), one BC and six Van-Veen (VV) samples at Ormonde seamount (SW Portugal continental platform), 16 VV samples at Formigas seamount (Azores Islands), and finally 13 VV samples at Chella Bank (NE Alboran Sea). Overall, sediment samples collected at Gazul corresponded to very fine sandy bottoms; deep sediment samples at Ormonde corresponded to very fine muddy sands, whereas shallowest ones corresponded to medium-fine sands, in some cases with a high proportion of gravels, and a moderate to low %mud; at Formigas, sediment samples corresponded to fine-very fine and medium-fine sandy bottoms, with %mud increasing with depth; whereas sediments collected at the SW sector of Chella Bank corresponded to muddy sands, most E sampling stations displayed fine-very fine sandy bottoms with a high % mud and abundant coral remains, and samples collected at the S sector corresponded to medium-fine and very fine sands, with a moderate %mud.